2015
DOI: 10.1186/s12940-015-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate concentrations in house dust in relation to autism spectrum disorder and developmental delay in the CHildhood Autism Risks from Genetics and the Environment (CHARGE) study

Abstract: BackgroundPhthalates are endocrine-disrupting chemicals that influence thyroid hormones and sex steroids, both critical for brain development.AimWe studied phthalate concentrations in house dust in relation to the risks of developing autism spectrum disorder (ASD) or developmental delay (DD).MethodsParticipants were a subset of children from the CHARGE (CHildhood Autism Risks from Genetics and the Environment) case–control study. ASD and DD cases were identified through the California Department of Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 34 publications
6
45
1
2
Order By: Relevance
“…Bi et al observed in the test house that the concentration of BBzP in dust deposited on the floor was about 20‐30 times higher in comparison with non‐floor dust, with little differences observed for DEHP. Similar experimental findings were found by Sukiene et al Other studies have shown that the concentrations of defined phthalates in indoor dust (BBzP and DEHP) were significantly higher in homes with PVC flooring when compared with other flooring materials …”
Section: Introductionsupporting
confidence: 88%
“…Bi et al observed in the test house that the concentration of BBzP in dust deposited on the floor was about 20‐30 times higher in comparison with non‐floor dust, with little differences observed for DEHP. Similar experimental findings were found by Sukiene et al Other studies have shown that the concentrations of defined phthalates in indoor dust (BBzP and DEHP) were significantly higher in homes with PVC flooring when compared with other flooring materials …”
Section: Introductionsupporting
confidence: 88%
“…Among autism and development delay boys, higher indoor dust concentrations of were associated with greater hyperactivityimpulsivity and inattention [104].…”
Section: Diethyl Phthalate and Dibutylphthalatementioning
confidence: 93%
“…It has been reported that the residues of PAEs were detected in various environmental matrices, such as air (Teil et al, 2006;Tran and Kannan, 2015), soil (Net et al, 2015;Niu et al, 2014), water and sediment (Peijnenburg and Struijs, 2006;Selvaraj et al, 2015). Researchers have indicated that some PAEs have endocrine disruptive effects in animals and humans (Main et al, 2006;Philippat et al, 2015;Zota et al, 2014). Therefore, the environmental behavior and potential human health risks of PAEs have attracted considerable attention.…”
Section: Introductionmentioning
confidence: 98%